The closo‐Dodecaborate Dianion Fused with Oxazoles Provides 3D Diboraheterocycles with Selective Antimicrobial Activity. Issue 41 (5th July 2018) - Sun, Yuji; Zhang, Jianglin; Zhang, Yuanbin; Liu, Jiyong; van der Veen, Stijn; Duttwyler, Simon
Abstract: The synthesis and application of icosahedral boron cluster compounds has been studied extensively since their discovery several decades ago; however, two aspects of their chemistry have received little attention: The possibility to form inorganic/organic fused boraheterocycles and their potential to act as antimicrobial agents. This work comprises the preparation of a class of 3D diborabenzoxazole analogues with the closo ‐dodecaborate in place of the benzene moiety. The presented synthetic procedures provide access to a wide range of diboraheterocycles under mild conditions. These 3D heterocycles exhibit strong and selective antimicrobial activity against Neisseria gonorrhoeae, a widespread bacterial pathogen that has shown increasing incidences of multidrug resistance and for which the development of new antimicrobial compounds is urgently needed. Abstract : An efficient synthetic methodology has been developed that provides access to dodecaborate amides and fused dodecaborate–oxazole heterocycles (see scheme). The procedures are mild, high yielding, and allow for structural diversity. Strong and selective bactericidal activity against Neisseria gonorrhoeae was observed for the 3D heterocycles.